Effects of a Program of Obesity’s Rehabilitation in an under Developed Country - ALAGNIDE, Etienne; Gandema, Salif; NIAMA NATTA, DIDIER; HOUNGBEDJI, M. GERMAIN; Okou, Laurence S.; KPADONOU GODONOU, TOUSSAINT (My University, 2021)
Background: Obesity is a major public health concern. Objective: To analyze effects of a rehabilitation program on adult obese in Cotonou. Methods: It was a prospective, cross-sectional, descriptive and analytical study, conducted from January to June 2016 (06 months), on 122 adult obese subjects, recruited in some gymnastics clubs and the Department of Physical Medicine and Rehabilitation of the CNHU-HKM of Cotonou. A program of physical activity were done during 20 sessions. Clinical and biological parameters were evaluated in these subjects before and after the program. Comparing the beginning and ending values of those parameters, their evolution were evaluated. Results: Most of these patients were females (94.26%) aged 46.3 ± 9.70 years. Their mean BMI was 37.26 ± 5.04 kg/m2 with an android obesity (45.9%) or a mixed one (54.1%). The fat mass index (FMI) was 47.95 ± 7.56%. Hypercholesterolemia (59.02%) and hypertriglyceridaemia (9.02%) were observed at the beginning of the program. At the end of the rehabilitation program, anthropometric parameters of patients were improved more markedly than those of lipids. No clinical or biological parameters studied were significantly associated with patient’s BMI and FMI changes (p>0.05). Conclusion: The exercise program has shown encouraging results and is therefore interesting to be applied to a larger population in underdeveloped countries.
Keywords: Obesity; Rehabilitation; Physical activity; Cotonou